Analysis of error in mathematical modeling problems: An exploratory study of middle school students - Permata, Jeliana Intan; Budiarto, Mega Teguh; Fuad, Yusuf (Edelweiss Applied Science and Technology, 2025)
This study analyzes students’ errors in solving mathematical modeling problems based on their mathematical ability levels through a quantitative, descriptive, and exploratory approach. It involves 72 eighth-grade students at a private school, SMP St. Benediktus. The instruments used are the Mathematical Competence Test (MCT) and the Mathematical Modeling Test (MMT). Both instruments were validated by three associate professors and one mathematics teacher, with validity confirmed by V Aiken’s coefficient of 0.83, exceeding the threshold of 0.4. Students completed the MCT and MMT on separate days. Based on the results, students were classified as high (20), medium (19), and low ability (33). MMT responses were analyzed using Newman Error Analysis and the six modeling processes from the Blum and Leiß framework. The results show that 67 students made errors across various stages, mainly in validating (47.56%) and understanding (31.59%), simplifying (37.84%), and mathematizing (39.58%). High-ability students often made errors in interpreting (18%) and validating (25%) processes, medium-ability students in working mathematically (25%), and low-ability students in understanding (38.75%). These results suggest that error types are closely related to students’ mathematical abilities. Further research should focus on aligning instruction with student abilities, supporting adaptive learning, and exploring targeted interventions to address specific errors in the modeling process.